Sophisticated and naïve procrastination: An experimental study - Claudia Cerrone; Leonhard K. Lades (Max Planck Institute for Research on Collective Goods, 2017)
The model of time-inconsistent procrastination by O'Donoughe and Rabin shows that individuals who are not aware of their present-bias (naïve) procrastinate more than individuals who are aware of it (sophisticated) or are not present-biased (time-consistent). This paper tests this prediction. We classify participants into types using a novel measure, and require them to perform a real-effort task on one out of three dates. We find that sophisticated participants perform the task significantly later than naïve participants. Our data suggest that this result may be explained by habit formation.
Keywords: C70; C91; D03; D91; 330; procrastination; present-bias; habit formation